Analisis Kealpaan yang Mengakibatkan Matinya Orang Ditinjau dari Pasal 359 KUHP: Studi Kasus Putusan Perkara No. 952k/Pid/2010 - Rondonuwu, Patrice; Suhendar, Tubagus Ahmad (Jurnal Hukum dan Demokrasi (JHD), 2024)
The Criminal Code in force in Indonesia, regarding criminal acts that result in the death of a person in "Title five years or a maximum prison sentence of one year, while Article 360 of the Criminal Code states "Due to his fault (culpa) causing a person to be seriously injured or injured so that the person becomes temporarily ill or unable to carry out his position or work temporarily." When the Criminal Code was formed, conscious negligence was a more serious form than unconscious negligence. This means that the pattern of simple negligence is that people use violations of the law without realizing it at all. He didn't know, didn't think it through first or was wise. But a more serious type of negligence is conscious negligence, that is, if at the time of action the possibility of causing a prohibited consequence was realized, but because of intelligence or the absence of actions to prevent it, it was hoped that this possibility would not arise.